Course on health & safety in tunnelling (Thomas Telford, 1998)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a course held at Royal Holloway University of London, Egham on 8-9 September 1998.
Keywords: Tunneling -- Safety measures -- Congresses.; elektronické knihy; electronic books